EFFICACY OF FIRST LINE MONOCHEMOTHERAPY IN ADVANCED GASTRIC CANCER (Vietnam Journal of Community Medicine, 2026)
Background: Advanced / Metastatic gastric cancer has a short survival prognosis despite many advances in treatment. In particular, in the group of elderly patients, with many comorbidities and poor performance status score, a specific treatment strategy is needed. Monochemotherapy is the preferred treatment. Therefore, our study aimed to evaluate the efficacy and safety of monochemotherapy in this group of patients.Methods: Retrospective study describing a series of cases. Patients with recurrent, advanced, metastatic gastric cancer who had not received previous systemic treatment were then treated with a monochemotherapy regimen with or without targeted therapy at the Department of Breast, Gastroenterology, Hepatology, and Urology, Ho Chi Minh City Oncology Hospital from January 1, 2023 to April 30, 2024.Results: The analysis included 58 patients (median age 65 years); 93% of patients had ECOG ≥1. 41.4% of patients had other comorbidities. 62.1% of patients were initially treated with TS-1, followed by Capecitabine (13.8%). The ORR and DCR were 18.9% and 55.1%, respectively. 32.8% received second-line and beyond therapy. Median PFS was 4 months and median OS was 5 months. Toxicities were mostly grade 1 and 2. The most common adverse events were anemia (32.8%), and nausea (31.1%). No deaths due to toxicity were recorded. No differences in survival were observed in different subgroups according to age, treatment regimen, or metastatic location.Conclusions: Monochemotherapy regimens may be a safe option for a special group of elderly patients, those with poor PS and multiple cormobidities.
Keywords: gastric cancer, advanced and metastatic, monochemotherapy, first-line